THE IMPLEMENTATION OF SCHOOL HEALTH UNITS BASED ON WORK TEAM AND TRIAS UKS IN THE PRIMARY SCHOOLS: SCHOOL HEALTH UNITS - Gisely Vionalita; Devi Angeliana Kusuma Ningtiar; Sella Puspita Sari (STIKes Mandala Waluya Kendari, 2022)
Background: The proper management of School Health Units (in Indonesian abbreviation as “UKS”) in educational institutions has the ability to sustain health behavior and optimize student growth and development. As evaluation of the program is a reliable process to measure efficiency and effectiveness of their activities, we aimed to report the evaluation of development the UKS work team and the Three Main Programs of Schools Health Units (TRIAS UKS) in Ngawen Subdistrict, Blora Regency as an indicators’ for Indonesia health research networks and programs. Methods: This is a quantitative descriptive research with data obtained from principals of 30 Primary Schools by using purposive sampling. The evaluation using the work team form and TRIAS UKS form indicators, including health education, health services and healthy school environments, is designed to profile the development of school health program. Results: Based on those indicators, the UKS work team still had problems in showing the decree on the organization of UKS team. In terms of health education, many of the schools hd lack of media to promote health. The schools also had difficulties in doing some consultation for mental health for students and some of schools were unsuccessful developing the healthy canteen. Conclusion: Research evaluation the UKS work team and TRIAS UKS are important elements in the success of the School Health Units (UKS). Thus, it creates constructive positive learning process and provides an overview of the limitations and challenges which can be used for better planning and promotion of the health research system nationally and globally.